PENERAPAN ORNAMEN KHAS BETAWI DALAM INTERIOR MASJID RAYA KH. HASYIM ASYARI JAKARTA BARAT - Ayesya Ainun Nabila; Ayu Safira Septiana; Githa Nabila; Resky Annisa Damayanti (Universitas Trisakti, 2020)
Abstract The Mosque is the buildings of worship for Muslims who can accommodate the worshipers. In the Mosque’s interior design is identical to the use of typical Middle Eastern ornaments such as calligraphy, but over time the Mosques in Indonesia have begun to apply the special ornaments of the area where the Mosque is located, for example the Great Mosque KH Hasyim Asyari which applying Betawi ornaments to the exterior and interior. Betawi ornaments themselves are identical applied to Betawi traditional houses, for example Gigi Balang ornaments that are applied to the house’s lisplang, and also Tapak Dara ornaments that are applied to railing porch railings. Nowadays the application of Betawi ornaments is not only in traditional houses but also in public buildings such as Mosques. The purpose of this research is to discuss the application of Betawi ornaments and the meanings contained in the ornaments. The results of this study are the application of Betawi special ornaments on the interior of the Great Mosque K.H Hasyim Asyari where it is placed on the walls, railings, and pillars of the Mosque. The typical Betawi ornaments that are applied are the Gigi Balang ornament, Tapak Dara, and also the shape of the Betawi traditional house roof which is designed in such a way that it becomes an ornament applied to the Mosque’s pulpit walls. It can be concluded that the application of Betawi special ornaments can not only be applied to traditional houses but also exist in other buildings with modifications in such a way but do not leave the meaning contained in the ornaments. AbstrakMasjid merupakan bangunan tempat beribadah bagi umat islam yang dapat menampung jamaah. Pada desain interior Masjid identik dengan penggunaan ornamen khas Timur Tengah seperti misalnya kaligrafi, namun seiring berjalannya waktu Masjid-Masjid yang berada di Indonesia sudah mulai menerapkan ornamen-ornamen khas daerah tempat Masjid itu berada, sebagai contoh Masjid Raya K.H Hasyim Asyari yang menerapkan ornamen Betawi pada eksterior dan interiornya. Ornamen khas Betawi sendiri identik diterapkan pada rumah adat Betawi misalnya ornamen Gigi Balang yang diterapkan pada lisplang rumah, dan juga ornamen Tapak Dara yang diterapkan pada railing pagar teras rumah. Kini penerapan ornamen Betawi tidak hanya pada rumah adat tetapi juga pada bangunan-bangunan umum seperti pada Masjid. Tujuan penelitian ini adalah untuk membahas mengenai penerapan ornamen khas Betawi dan juga makna yang terkandung dalam ornamen tersebut. Hasil dari penelitian ini adalah adanya penerapan ornamen khas Betawi pada interior Masjid Raya K.H Hasyim Asyari di mana peletakannya berada pada dinding, railing, dan pilar Masjid. Ornamen khas Betawi yang diterapkan yaitu ornamen Gigi Balang, Tapak Dara, dan juga bentuk atap rumah adat Betawi yang di desain sedemikian rupa sehingga menjadi ornamen yang diterapkan pada bagian dinding mimbar masjid. Dapat disimpulkan bahwa penerapan ornamen khas Betawi tidak hanya dapat diterapkan pada rumah adat tetapi juga eksis diterapkan di bangunan lain dengan modifikasi sedemikian rupa namun tidak meninggalkan makna yang terkandung di dalam ornamen tersebut